2021
DOI: 10.3389/fphar.2021.660757
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities and Mechanisms of Hirudin and Its Derivatives - A Review

Abstract: Hirudin, an acidic polypeptide secreted by the salivary glands of Hirudo medicinalis (also known as “Shuizhi” in traditional Chinese medicine), is the strongest natural specific inhibitor of thrombin found so far. Hirudin has been demonstrated to possess potent anti-thrombotic effect in previous studies. Recently, increasing researches have focused on the anti-thrombotic activity of the derivatives of hirudin, mainly because these derivatives have stronger antithrombotic activity and lower bleeding risk. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 169 publications
1
50
0
Order By: Relevance
“…It is worth noting that studies have shown that hirudin improves myocardial infarction by inhibiting oxidation ( Zhang H. et al, 2020 ), and can also protect AngII-induced myocardial fibroblast fibrosis by inhibiting extracellular signal-regulated kinase ( Yu et al, 2018 ). Cell hypertrophy and fibrosis are an important pathophysiological process in myocardial remodeling, and it is not difficult to speculate that hirudin also plays an important role in the treatment of cardiac hypertrophy, which may be beneficial for the treatment of cardiac hypertrophy due to its extensive pharmacological activities ( Junren et al, 2021 ), but on the other hand, the property of polypeptides may make it difficult to study the underlying mechanisms in depth. The network pharmacology approach integrating systems biology and computer technology can provide directions for the mechanistic study of complex botanicals or compounds ( Nowak, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that studies have shown that hirudin improves myocardial infarction by inhibiting oxidation ( Zhang H. et al, 2020 ), and can also protect AngII-induced myocardial fibroblast fibrosis by inhibiting extracellular signal-regulated kinase ( Yu et al, 2018 ). Cell hypertrophy and fibrosis are an important pathophysiological process in myocardial remodeling, and it is not difficult to speculate that hirudin also plays an important role in the treatment of cardiac hypertrophy, which may be beneficial for the treatment of cardiac hypertrophy due to its extensive pharmacological activities ( Junren et al, 2021 ), but on the other hand, the property of polypeptides may make it difficult to study the underlying mechanisms in depth. The network pharmacology approach integrating systems biology and computer technology can provide directions for the mechanistic study of complex botanicals or compounds ( Nowak, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hirudin is mainly a polypeptide substance, isolated and purified from the saliva of leech, and it is the strongest natural anticoagulant among the known substances found in the world so far ( Dong et al, 2016 ; Junren et al, 2021 ). Hirudin is a promising anticoagulant drug, a large number of studies have indicated that hirudin has the functions of inhibiting platelet aggregation, reducing blood lipids, regressing atherosclerosis, promoting the absorption of cerebral hematoma, and relieving intracranial pressure ( Azzopardi et al, 2011 ; Bian et al, 2020 ; Junren et al, 2021 ; Nilius et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main component of MXK is Hirudo nipponic a Whitman (Haemadipsidae, Hirudo) which is the strongest natural thrombin-specific inhibitor discovered yet ( Junren et al, 2021 ). Hirudin inhibits thrombin activity by directly binding with thrombin and plays an anticoagulant role.…”
Section: Discussionmentioning
confidence: 99%
“…The active chemical secretions of H. manillensis into the host blood not only facilitate the blood-sucking behavior but also have important implications in medicine and clinical practice. Classically, hirudin-HM not only specifically binds to thrombin and causes anticoagulation, which enhances the fibrinolysis, but also has the functional role of anti–myocardial infarction, treatment of organic-type coronary arterial disease, and anti–deep vein thrombosis ( De Filippis et al, 1995 ; Junren et al, 2021 ; Zhang et al, 2020 ). Furthermore, several other active substances with anticoagulant, anti-inflammatory, and analgesic properties have already been identified ( Guan et al, 2019 ; Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%